Women Politeness Strategies from Different Professions on a YouTube Dating Show - Siska Ristanti; Cipto Wardoyo; Erfan Muhamad Fauzi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines the use of politeness strategies by women on the YouTube dating show Pop the Balloon or Find Love. This research is grounded in the critical role of politeness strategies in preserving interpersonal relationships and self-image within romantic interactions in digital public spaces. The objective of this study is to identify the types of politeness strategies used by women and to analyze variations in their use based on the participants’ professional backgrounds. This study employs a qualitative descriptive method using a directed qualitative content analysis approach based on Brown and Levinson’s (1987) theory of politeness strategies. A total of 153 utterances containing politeness strategies were successfully identified. The results indicate that all types of politeness strategies were present in the data, with positive politeness being the most dominant strategy, reflecting participants’ tendency to build interpersonal closeness and maintain a positive image of the interlocutor. Furthermore, variations in the use of politeness strategies were found based on profession, although the context of interaction and communication goals also influenced strategy selection. These findings suggest that professional background contributes to the tendency to use politeness strategies in digital romantic interactions.